DEVELOPMENT MATHEMATIC MODULE OF QUADRILATERAL AND TRIANGLE MATERIAL FOR STUDENTS - Mita Pramesti; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The availability of teaching materials based on the 2013 curriculum to facilitate students to self-study actively and independently is still limited. The quadrilateral and triangle material math modules are some of the alternative teaching materials used to actively facilitate active learning. This study aims to develop a quadrilateral and triangle material mathematical module for students of class VII SMP / MTs based on the 2013 curriculum and know the feasibility of modules developed based on material experts, media experts, and student responses. This research type is the research of development, in the form of math material module of quadrilateral and triangle for class VII student of Junior High School (SMP/MTs) based on curriculum 2013. In developing this module, the researcher refers to the model development of ADDIE covering five stages: analysis, design, Development, Implementation, and Evaluation. The instruments used in this research are the assessment sheets for the material expert, the assessment sheet for the media expert, and the student response questionnaire. This study's subjects are material experts, media experts, and students of SMP Negeri 15 Yogyakarta and MTs Muhammadiyah Karangkajen. Data collection technique collection in the form of interviews and questionnaires. The results of this research and development show that the module. The mathematics developed included in the category is very well based questionnaire assessment by a material expert with a score of 136,67; Questionnaire assessment by experts media with a score of 126,33; and average student response results in this study is 130,05. The assessment results show that the mathematics module quadrilateral and triangular materials for grade VII students of SMP / MTs based on the 2013 curriculum are worthy of use in the learning process.